Crescentic glomerulonephritis: data from the Spanish Glomerulonephritis Registry. Issue 5 (May 2015) - Quiroga, B.; Vega, A.; Rivera, F.; López‐Gómez, J. M.; the Spanish Registry of Glomerulonephritis
Abstract Background Crescentic glomerulonephritis (CGN) is a histological finding that implies rapid deterioration of renal function and can be related to different diseases, such as type 1 or anti‐glomerular basement membrane antibody (Goodpasture) disease, type 2 or immune complex CGN and type 3 or pauci‐immune disease. Aim The present study describes CGN and its characteristics based on the data from the Spanish Glomerulonephritis Registry. Methods An analysis was made of all native renal biopsies obtained from patients during 1994–2013 and classified as CGN. A patient epidemiological and clinical data questionnaire was completed by the 120 centres involved. Results A total of 21 774 biopsies was performed, of which 2089 (8.1%) corresponded to CGN (211 type 1, 177 type 2 and 1701 type 3). Renal function was poorer in type 1 compared with types 2 and 3, and proteinuria was higher in type 2 compared to types 1 and 3. Patients diagnosed with CGN type 3 were older than those with types 1 and 2, but less hypertensive than the type 2 patients. No differences in the urine test findings were found between types 1 and 2. Microhaematuria was the most frequent feature in general, as well as in type 3 compared with types 1 and 2. The main indication for biopsy was acute renal injury. Age was the only difference between type 1 patients with and without alveolar haemorrhage (53 [33–67] vs 64 [46–73], P = 0.008). Conclusion Although classified as the same entity, the different types of CGN have different features that must be taken into account.